A superspreading event involving a cluster of 14 coronavirus disease 2019 (COVID-19) infections from a family gathering in Hong Kong SAR (China) (Western Pacific Surveillance and Response, 2020)
Objective: An outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first reported in Wuhan, China, in December 2019, with subsequent spread around the world. Hong Kong Special Administrative Region SAR (China) recorded its first confirmed cases on 23 January 2020. In this report, we describe a family cluster of 12 confirmed cases, with two additional confirmed cases from secondary transmission.Methods: We reported the epidemiological, clinical and laboratory findings of the family cluster, as well as the public health measures instituted.Results: All 12 confirmed COVID-19 cases were among the 19 attendees of a three-hour Chinese New Year family dinner consisting of hotpot and barbecue dishes. Environmental sampling of the gathering venue was negative. Two additional confirmed cases, who were co-workers of two confirmed cases, were later identified, indicating secondary transmission. Contact tracing, quarantine and environmental disinfection were instituted to contain further spread.Discussion: Our findings were highly suggestive of a superspreading event during the family gathering. The source was likely one of the cases during the pre-symptomatic phase. The event attested to the high infectivity of SARS-CoV-2 through human-to-human transmission from social activities and argued for the necessity of social distancing in curtailing the disease spread.